Current Understanding of the Molecular Basis of Venezuelan Equine Encephalitis Virus Pathogenesis and Vaccine Development - Sharma, Anuj; Knollmann-Ritschel, Barbara (Viruses, 2019)
Venezuelan equine encephalitis virus (VEEV) is an alphavirus in the family Togaviridae. VEEV is highly infectious in aerosol form and a known bio-warfare agent that can cause severe encephalitis in humans. Periodic outbreaks of VEEV occur predominantly in Central and South America. Increased interest in VEEV has resulted in a more thorough understanding of the pathogenesis of this disease. Inflammation plays a paradoxical role of antiviral response as well as development of lethal encephalitis through an interplay between the host and viral factors that dictate virus replication. VEEV has efficient replication machinery that adapts to overcome deleterious mutations in the viral genome or improve interactions with host factors. In the last few decades there has been ongoing development of various VEEV vaccine candidates addressing the shortcomings of the current investigational new drugs or approved vaccines. We review the current understanding of the molecular basis of VEEV pathogenesis and discuss various types of vaccine candidates.